American Literary History and the Turn toward Modernity - Goldsmith, Meredith; Dawson, Melanie, 1967- (Book collections on Project MUSE., 2018)
Approaching the period of 1880-1930 in American literature as one in which the processes of rethinking the past were as prevalent as wholly "new" works of art, this collection treats the century's long turn as a site that overtly staged the tension among conflicting sets of values--those of past, present, and the imagined future. As the authors of this collection demonstrate, the literature from the century's turn is irreducible to the characteristics either of the nineteenth or the twentieth centuries; rather, it is literature of dual practices and multiple values that embodies elastic qualities of historical plurality--a true literature in transition